2017
DOI: 10.1016/s1473-3099(17)30339-0
|View full text |Cite|
|
Sign up to set email alerts
|

Improving communication about viral hepatitis in Africa

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…This review also found only limited information regarding patient‐reported barriers to adherence, and there is a need for a better understanding of causes of nonadherence. More fundamentally, there is a need to improve awareness of the disease; in many low‐income settings, knowledge of HBV in the general population is very limited, with less than 1% of people in The Gambia reporting to have heard of hepatitis B, although most are familiar with HIV and malaria . Future research should focus both on identification of potential risk factors (including age, sex, coinfection status, and stage of disease) and patient‐reported barriers to help identify patients at higher risk of nonadherence and supportive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This review also found only limited information regarding patient‐reported barriers to adherence, and there is a need for a better understanding of causes of nonadherence. More fundamentally, there is a need to improve awareness of the disease; in many low‐income settings, knowledge of HBV in the general population is very limited, with less than 1% of people in The Gambia reporting to have heard of hepatitis B, although most are familiar with HIV and malaria . Future research should focus both on identification of potential risk factors (including age, sex, coinfection status, and stage of disease) and patient‐reported barriers to help identify patients at higher risk of nonadherence and supportive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Undiagnosed cases in low‐ to middle‐income countries (LMIC) are also found in these key populations, but the greater problem lies in limited centralized diagnostic facilities, cost of testing, lacking public education and awareness, and need for skilled health professionals . Improving general understanding of viral hepatitis and its health consequences are also central to increasing disease awareness and could be addressed via public health campaigns .…”
Section: Discussionmentioning
confidence: 99%
“…Previous sub-Saharan African studies have found a lack of recognition of the term "hepatitis B" among lay publics and limited knowledge among health-care workers, for which there are numerous reasons. [9][10][11][12][13][14][15][16][17] The natural history of chronic HBV infection is complex: following exposure to HBV at birth or during early childhood, a lengthy period ensues during which chronic HBV infection is asymptomatic until the development of end-stage liver disease (jaundice, ascites, hematemesis, and weight loss). 18,19 Nonetheless, because signs and symptoms of end-stage liver disease are visible, understanding how African lay populations explain these physical symptoms would be useful.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted this investigation to provide the foundations for strengthening communications strategies to enhance scale-up of screening and treatment services in Senegal and other African countries. 14…”
Section: Introductionmentioning
confidence: 99%